The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/es060157c
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Deposition of Current-Use and Historic-Use Pesticides in Snow at National Parks in the Western United States

Abstract: The United States (U.S.) National Park Service has initiated research on the atmospheric deposition and fate of semi-volatile organic compounds in its alpine, sub-Arctic, and Arctic ecosystems in the Western U.S. Results for the analysis of pesticides in seasonal snowpack samples collected in spring 2003 from seven national parks are presented herein. From a target analyte list of 47 pesticides and degradation products, the most frequently detected current-use pesticides were dacthal, chlorpyrifos, endosulfan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
139
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(149 citation statements)
references
References 30 publications
8
139
1
Order By: Relevance
“…In recent years, most data on CUPs in atmospheric and aquatic environment published in international journals were from North America. 4,6,8,9,11,16 That indicates most current studies are not more than nationwide, but actually sampling sites in the majority of studies even covered only a small geographical area (a small Environmental Science & Technology ARTICLE part of a country). Thus the global CUPs distribution is not well understood.…”
Section: ' Introductionmentioning
confidence: 99%
“…In recent years, most data on CUPs in atmospheric and aquatic environment published in international journals were from North America. 4,6,8,9,11,16 That indicates most current studies are not more than nationwide, but actually sampling sites in the majority of studies even covered only a small geographical area (a small Environmental Science & Technology ARTICLE part of a country). Thus the global CUPs distribution is not well understood.…”
Section: ' Introductionmentioning
confidence: 99%
“…As observed in the polar regions (Cabrerizo et al, 2012;Halsall, 2004), field studies in Europe , western Canada (Davidson et al, 2003), South America (Grimalt et al, 2004a;Pozo et al, 2007) and the Tibetan Plateau among others, have shown that mountains can act as cold-traps for POPs or even organic compounds with limited atmospheric transport, e.g. currently used pesticides (Hageman et al, 2006). These previous studies have documented the overall accumulation process but the mechanisms by which these compounds are transported through the atmosphere and accumulate in these environments are largely unknown.…”
Section: Introductionmentioning
confidence: 91%
“…Second, snowpack samples collected at the end of winter represent integration of chemical input over many months, whereas summertime samples may reflect conditions over much shorter time intervals. Third, although contaminant inputs are primarily regional during both summer and winter [8,28], contaminant inputs likely vary spatially more during summer than winter due to the more localized wind patterns during summer (e.g., up-valley winds [28]) than the widely circulating cyclonic storms during winter.…”
Section: Variability In Chemical Concentrationsmentioning
confidence: 99%
“…The present study focuses on the Sierra Nevada mountain range, which lies adjacent to one of the highest agricultural pesticide-use areas in North America, the Central Valley of California [4]. Even in the remote alpine zone at high elevation (i.e., near or above timberline, >2,750 m), the occurrence of pesticides and other airborne contaminants is well documented [5][6][7][8][9][10], and concern has arisen that airborne contaminants may be having adverse effects on biota at high elevation. For example, concentrations of DDT-related compounds and dieldrin in fish from the southern Sierra Nevada at high elevation exceeded human health thresholds for recreational fishing and/or wildlife health thresholds [11], and dichlorodiphenyldichloroethylene (DDE) in lake sediment exceeded guidelines for protection of benthic organisms [10].…”
Section: Introductionmentioning
confidence: 99%